Pemetaan Potensi Pemasaran Dalam Penjualan Produk Anyaman Pandan Dusun 3 Pantai Cermin Kanan - Mesran; Ningsih, Trans; Suginam (Forum Kerjasama Pendidikan Tinggi, 2023)
The purpose of this community service activity is to provide understanding and assistance in evaluating marketing potential in the sale of pandan woven products in Dusun 3 Pantai Cermin Kanan. This community service activity is carried out by providing counseling in the form of outreach to the craftsmen of Pandan Menday Gallery & Souvenir. Through this activity, it is hoped that the craftsmen, especially the heads of the craftsmen's group, can determine the market share of the products made so that the range of product sales is wider. The participants in this community service activity totaled 23 craftsmen. The results of this community service are mapping product marketing first starting with recognizing business identity, namely by conducting a business SWOT analysis, strengthening business image/brand, then understanding the market by determining product STP stratgey.